Numerical study of an external device for the improvement of the thermal stratification in hot water storage tanks. (5th November 2018) - Gómez, M.A.; Collazo, J.; Porteiro, J.; Míguez, J.L.
Highlights: A CFD model is presented to simulate the thermal behaviour of a water storage tank. The model is applied to study the heating process and the steady state of new designs. An external device concentrates the heat exchange and improves thermal stratification. An improvement in the stratification allows to reduce the DHW heating times. Abstract: In this work, we study the operation of a water heater storage tank using CFD modelling and analyse its limitations in order to propose a redesign that improves its characteristics. The study method is based on calculating the main variables that affect the thermal performance using the finite volume method. With this method, the Navier-Stokes equations are applied to calculate the internal movements of the fluid and its heat exchange with the coil. A determining factor for the operation of a water heater tank is natural convection, which is solved by means of the Boussinesq approximation. Different reservoir simulations are carried out in continuous operation mode (stationary) and in heating mode (transient). In both cases, the results show very homogeneous heating, which means poor temperature stratification. As an alternative for improvement, a redesign of the system is proposed by means of an auxiliary tank where the heating coil is located, which injects the hot water, at different heights, into the main tank. Several simulations of this redesign are carried out with different configurations in order to achieve better temperature stratification, reduce the heating time and maintain the outlet temperature of the domestic hot water (DHW) between 45 and 60 °C. As a result, the redesign significantly improves the stratification of temperatures and reduces the heating time necessary to obtain a DHW temperature of 45 °C from 45 to 8 min.